2009
DOI: 10.1021/nl900250g
|View full text |Cite
|
Sign up to set email alerts
|

Selective Excitation and Detection of Spin States in a Single Nanowire Quantum Dot

Abstract: We report exciton spin memory in a single InAs(0.25)P(0.75) quantum dot embedded in an InP nanowire. By synthesizing clean quantum dots with linewidths as narrow as about 30 microeV, we are able to resolve individual spin states at magnetic fields on the order of 1 T. We can prepare a given spin state by tuning excitation polarization or excitation energy. These experiments demonstrate the potential of this system to form a quantum interface between photons and electrons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
83
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 28 publications
2
83
0
Order By: Relevance
“…GaAs/AlGaAs 7 , GaAs/GaP 12 and InP/InAs 13 core-shell NWs. Also axial NW heterostructures 7,14 become feasible that comprise segments of different semiconductor material with nanometer thickness along the NW [15][16][17] . Another interesting type of axial heterostructures uses alternating few nm short segments of the same chemical material but different crystal structure as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…GaAs/AlGaAs 7 , GaAs/GaP 12 and InP/InAs 13 core-shell NWs. Also axial NW heterostructures 7,14 become feasible that comprise segments of different semiconductor material with nanometer thickness along the NW [15][16][17] . Another interesting type of axial heterostructures uses alternating few nm short segments of the same chemical material but different crystal structure as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the combination of Si sections, which are free of nuclear spins, with optically addressable electronic levels in III-V materials is promising for extending electron spin storage times. Prior to the work presented here, we have shown that a single InAsP quantum dot grown in an InP nanowire geometry is optically active, exhibits narrow emission lines, spin polarization memory effects, 10 and can be embedded in a LED device geometry. 11 Furthermore, it is predicted that NW-QDs are ideal sources of entangled photons due to the nanowire symmetry.…”
mentioning
confidence: 96%
“…By energy dispersive X-ray analysis in a transmission electron microscope, the dot size for 2 s of growth was estimated to be 9 ( 1 nm high and 33 ( 1 nm in diameter. 10 After growth, the InP nanowires were transferred from the InP growth substrate to a prepatterned p ++ silicon wafer with thermal oxide layer of 290 nm. Characterization by microphotoluminescence (µPL, see below) was done to select individual quantum dots with emission linewidths below 400 µeV.…”
mentioning
confidence: 99%
“…These defect-free pure ZB wires have high optical quality as concluded from the sharp emission peak (FWHM ¼ 2.3 meV) and are a promising platform for the integration of InAsP quantum dots. 25 It allows to precisely tuning the cross-sectional shape and length to tailor and minimize the fine structure splitting. 26 …”
mentioning
confidence: 99%